ANALISIS HUKUM EKONOMI SYARIAH TERHADAP TRANSAKSI BAYAR NANTI (PAYLATER) PADA APLIKASI SHOPEE: Pendahuluan, metode penelitian, hasil dan pembahasan, kesimpulan, daftar pustaka - Savila, Lisna Nisa; Kurniawati, Fitri; Gunawan, Ade (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Shopee is an application that facilitates online buying and selling. One of the products or offers in the shopee application is Shopee paylater which provides loans or installments for shopee users who buy goods on credit online. In this case, the researcher aims to find out the pay later transaction through the paylater from the shopee application based on sharia economic law. This research uses a qualitative research method that uses a library research approach. Based on the results of research and discussion, where based on sharia economic law there are two laws that allow and prohibit transactions using paylater. Where Shopee paylater brings harm to consumers because this feature provides benefits from users and this payment delay is usury because one of the conditions contains provisions for fines if it exceeds the previously agreed tempo, but in Islamic economic transactions the important thing is honesty. with honesty will bring goodness, happiness and trust so as to provide blessings.